Outcome of Pituitary Adenoma Surgery Through Transphenoidal Endoscopic Endonasal Approach -A Study of 96 Cases (Bangladesh Journal of Neurosurgery, 2024)
Background: Transphenoidal endoscopic approach is minimal invasive surgery in case of pituitary adenoma.Objective : To see the outcome of transphenoidal endoscopic approach in case of pituitary tumour.Results : This study showed among the 96 patients, 64 (66.7%) patients were male and 32(33.33%) were female. It was documented that in 96 patients, 88(91.66.3%) were macroadenoma and 8(8.33%) were microadenoma. Among 96 patients, 88 (91.66%) had preoperative visual disturbance and 8(8.33%) had normal vision. Tumor was totally removed in 88(91.66%) patients in endoscopic approach. Clinically 92(95.8%) patients were improved in endoscopically. Two (2.1%) patient developed pneumocephalus and meningitis, between them one died due to meningitis and other cured by conservative treatment. In 2 (2.1%) patient, carotid artery was partially torn, which was managed by nasal pack.Conclusion: It was concluded that endoscopic endonasal approach is safe and effective procedure.Bang. J Neurosurgery 2023; 12(2): 29-33